PEMAKNAAN KEPENASIHATAN AKADEMIK: SEBUAH STUDI FENOMENOLOGI DI PRODI AKUNTANSI UNIVERSITAS MADURA - Rosy Aprieza Puspita Zandra (Jurnal Penelitian Humaniora, 2018)
Qualified academic direction can encourage student involvement in a strong learning experience both inside and outside the classroom. Nevertheless, the usefulness of academic aims is felt differently on the experienced side. This study aims to describe the meaning of academic aims in the field of study of Accounting based on the subjective experience of informants. The method used in this research is qualitative type of phenomenology study. Informant selected purposively based on experience related to the research topic and his willingness to share stories about his experience. The findings of this research can be summarized as: (1) Interaction of Academic Advisory Indirectly Leads to the Value of Independence, namely that the student is the primary role holder in developing the potential and his ideas in self efficacy effort, while the lecturer plays the support by directing the students (2) Academic Advisory based on Humanistic Concern (3) Achievement of Academic Aims for the Field of Science.